2020
DOI: 10.1101/2020.12.10.20246959
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

First and second waves of coronavirus disease-19: A comparative study in hospitalized patients in Reus, Spain

Abstract: Many countries have seen a two-wave pattern in reported cases of coronavirus disease-19 during the 2020 pandemic, with a first wave during spring followed by the current second wave in late summer and autumn. Empirical data show that the characteristics of the effects of the virus do vary between the two periods. Differences in age range and severity of the disease have been reported, although the comparative characteristics of the two waves still remain largely unknown. Those characteristics are compared in t… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
62
2
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 100 publications
(71 citation statements)
references
References 27 publications
(32 reference statements)
5
62
2
2
Order By: Relevance
“…Additionally, improved testing capacities in the second wave could have resulted in more mild cases being identified (22,23,31,32); and healthcare systems in many countries could have been better prepared in the second wave, offering timely treatment of severe cases (20,22,30). Decreased mortality could also be related to the greater use of masks which, theoretically, could reduce the viral inoculum and perhaps disease severity (33).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, improved testing capacities in the second wave could have resulted in more mild cases being identified (22,23,31,32); and healthcare systems in many countries could have been better prepared in the second wave, offering timely treatment of severe cases (20,22,30). Decreased mortality could also be related to the greater use of masks which, theoretically, could reduce the viral inoculum and perhaps disease severity (33).…”
Section: Discussionmentioning
confidence: 99%
“…The studies included in our review showed a great deal of diversity. To minimize this factor as much as possible, we limited the review to papers on the first wave of COVID-19-between March and June 2020 [61,62]. We included only papers using validated tools and we focused only on symptoms of anxiety and depression; for clarity reasons, we did not analyze other psychological problems such as insomnia and post-traumatic stress disorder symptoms.…”
Section: Anxiety and Depression Symptoms In Pregnant Women And New Mothersmentioning
confidence: 99%
“…This study was conducted at the beginning of the second wave of COVID-19 in our region (27). The 14day cumulative incidence of COVID-19 cases in the city of Reus increased gradually from 0.9 cases/100,000 inhabitants on 15 June to 376.09 cases/100,000 inhabitants on 24 August (28).…”
Section: Description Of the Olfactory Testmentioning
confidence: 99%